Hubungan Pengetahuan dan Sikap dengan Kelengkapan Penggunaan APD Pada Pekerja PT X - Rini Angraini Harahap; Mardi Fadillah; Onetusfifsi Putra; Muhammad Iqbal Fahlevi; Safrizal Safrizal (KOLONI, 2026)
Personal Protective Equipment (PPE) represents an essential effort to reduce the occurrence of occupational accidents and must be worn by every worker. In practice, however, a number of workers remain non-compliant in wearing it while on duty. This research sought to examine how knowledge and attitude relate to the completeness of PPE use among employees of PT X. The study applied a cross-sectional design involving 36 workers who were determined through the total sampling technique. Information was gathered using questionnaires and subsequently processed with the Chi-Square test. Findings revealed no meaningful association between knowledge and the completeness of PPE use (p-value = 0.710), and likewise no meaningful association between attitude and the completeness of PPE use (p-value = 0.264). It is therefore concluded that neither knowledge nor attitude is linked to the completeness of PPE use among PT X workers. The findings are expected to provide a reference for the company in strengthening occupational health and safety practices through improved supervision and guidance.